Representasi Kesiapan Menikah, Peran Gender, dan Keluarga Ideal dalam Video “Lingsir”: Analisis Semiotika Roland Barthes - Dita Patresia; Susanne Dida; Elnovani Lusiana (Balai Bahasa Sulawesi Selatan, 2026)
This study aims to analyze the representation of marriage readiness, gender roles, and the concept of the ideal family in the video “Lingsir”, the winner of the AKUKAMU digital content competition organized by the National Population and Family Planning Board (BKKBN). This research employed a descriptive qualitative method. Data collection was conducted through the observation of visual and verbal signs within the video, categorized into eleven scenes across three blocks and supported by secondary data from official BKKBN documents and literature on reproductive health. The data analysis technique utilized Roland Barthes’ semiotic analysis, examining signs at the levels of denotation, connotation and myth. The results demonstrate that the video “Lingsir” constructs a contract between unprepared marriage as a chaotic situation and the idel marriage achieved through emotional, health, and knowledge readiness, including participation in the Pre-Marital School (Sekolah Calon pengantin, KUA counseling, and the 1000 Days of Life (1000 HPK) education. The findings also identify that women are still represented as the center of domestic responsibility and family health, while men are beginning to be portrayed as involved in the marriage preparation process. Overall, this video frames the ideal family as a unit that adheres to the guidance pathways provided by the state and religious institutions. AbstrakPenelitian ini bertujuan untuk menganalisis representasi kesiapan menikah, peran gender dan konsep keluarga ideal dalam video “Lingsir” pemenang lomba konten digital AKUKAMU yang diselenggarkan oleh BKKBN. Metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif. Teknik pengumpulan data dilakukan melalui observasi tanda visual dan verbal yang terdapat dalam video yang dikelompokkan ke dalam sebelas adegan dalam tiga blok serta didukung oleh data sekunder berupa dokumen resmi BKKBN dan literatur terkait kesehatan reprodusi. Teknik analisis menggunakan analisis semiotika Roland Barthes yang membedah tanda pada level denotasi, konotasi dan mitos. Hasil penelitian menunjukkan bahwa video “Lingsir” mengonstruksi kontras antara pernikahan tanpa persiapan sebagai situasi yang kacau dengan pernikahan ideal yang dicapai melalui kesiapan emosional, kesehatan dan pengetahuan termasuk partisipasi dalam Sekolah Calon pengantin, konseling KUA serta edukasi 1000 HPK. Temuan juga mengidentifikasi bahwa perempuan masih direpresentasikan sebagai pusat tanggung jawab domestik dan kesehatan keluarga sementara laki-laki mulai dicitrakan terlibat dalam proses persiapan pernikahan. Secara keseluruhan, video ini membingkai keluarga ideal sebagai unit yang patuh pada jalur pendampingan negara dan lembaga keagamaan.